PERSPECTIVE AND COMMUNICATION THEORY - Perdana, Muhammad Irfan; Nirmala, Sila (LPPM Univ. Ibn Khaldun Bogor, 2025)
Communication is an essential element of human existence. As social beings, humans cannot live without communication, as it enables them to interact, share meaning, and fulfill their social needs. This study employs a qualitative literature review approach to explore various communication theories and perspectives. The findings reveal that communication plays a fundamental role in human life as it facilitates the continuous exchange of messages and information among individuals. Moreover, communication can be understood through several theoretical perspectives, including the mechanistic, psychological, interactionist, and pragmatic perspectives. This study contributes to a deeper understanding of how communication theories explain human interactions across both social and digital contexts.